Not Frozen in the Ice: Large and Dynamic Rearrangements in the Mitochondrial Genomes of the Antarctic Fish. (11th February 2021) - Papetti, Chiara; Babbucci, Massimiliano; Dettai, Agnes; Basso, Andrea; Lucassen, Magnus; Harms, Lars; Bonillo, Celine; Heindler, Franz Maximilian; Patarnello, Tomaso; Negrisolo, Enrico
Abstract: The vertebrate mitochondrial genomes generally present a typical gene order. Exceptions are uncommon and important to study the genetic mechanisms of gene order rearrangements and their consequences on phylogenetic output and mitochondrial function. Antarctic notothenioid fish carry some peculiar rearrangements of the mitochondrial gene order. In this first systematic study of 28 species, we analyzed known and undescribed mitochondrial genome rearrangements for a total of eight different gene orders within the notothenioid fish. Our reconstructions suggest that transpositions, duplications, and inversion of multiple genes are the most likely mechanisms of rearrangement in notothenioid mitochondrial genomes. In Trematominae, we documented an extremely rare inversion of a large genomic segment of 5, 300 bp that partially affected the gene compositional bias but not the phylogenetic output. The genomic region delimited by nad5 and trnF, close to the area of the Control Region, was identified as the hot spot of variation in Antarctic fish mitochondrial genomes. Analyzing the sequence of several intergenic spacers and mapping the arrangements on a newly generated phylogeny showed that the entire history of the Antarctic notothenioids is characterized by multiple, relatively rapid, events of disruption of the gene order. We hypothesized that a pre-existing genomic flexibility of the ancestor of the Antarctic notothenioids may have generated a precondition for gene order rearrangement, and the pressure of purifying selection could have worked for a rapid restoration of the mitochondrial functionality and compactness after each event of rearrangement.